Sosialisasi Low Back Pain pada Kelompok Tani GAPOKTAN Wilayah Puskesmas Tawangmangu Karanganyar - Yussy Rha, Warda; kartika, Ayu prima; Faradhisa, Jihan; Sari, Rizqy Kartika; Nurriwanti, Nabylla Sharfina Sekar (Universitas Alifah Padang, 2025)
The members of the farmer group (Gapoktan) often report experiencing lower back pain, which is suspected to be related to work activities performed in a non-ergonomic manner. This is supported by data from the Self - Awareness Survey, which revealed that within a week, farmers can carry loads weighing between 0–100 kg directly by lifting them on their shoulders. This condition leads to symptoms of Low Back Pain (LBP), a common musculoskeletal disorder resulting from improper body posture during work. LBP is characterized by pain in the lower back area and can be caused by various factors such as congenital spinal abnormalities, physical trauma, changes in body tissue, or excessive weight-bearing. Although it is more commonly experienced by the elderly, LBP can also affect younger individuals. As an effort to enhance farmers’ understanding and awareness of LBP, a community service activity was conducted in November 2024. This event was attended by 16 local farmers. The method of implementation included a presentation on LBP, followed by a discussion and Q&A session. Additionally, pre-tests and post-tests were administered to assess participants’ knowledge before and after the session. The evaluation results showed a significant improvement in participants’ knowledge scores. This was evidenced by a statistically significant difference between the pretest and post-test scores, with a p-value of 0.001. Through this socialization exercise, it is intended that participants would learn more about low back pain.